On Isometric Extension in the Space sn(H). (21st October 2014) - Fu, Xiaohong
Abstract : We study the problem of isometric extension on a sphere of the spaces n ( H ) . We give an affirmative answer to Tingley's problem in the spaces n ( H ) .